Toxicological impact of rabeprazole and evaluation of toxic effects on the plant-based eukaryotic test models - Muhammad Torequl Islam; Marcello Iriti; Hicham Harhar; Youssef Elouafy; Imane Chamkhi; Eda Sönmez Gürer; Javad Sharifi-Rad (Vitae)
Background: Rabeprazole (RPZ), a widely used proton pump inhibitor, is known to have toxic effects on human beings. Objective: To evaluate the current understanding of its toxicological effects on humans and animals, a literature and laboratory-based study was conducted. Methods: A comprehensive search of published literature was conducted in various databases up until April 2020, using specific keywords. Additionally, toxic effects of RPZ-Na (0.025-0.4 mM) were evaluated on Allium cepa, Allium sativum and Cicer arietinum at different exposure times using CuSO4 as a reference standard. Results: The literature review revealed that RPZ has a wide range of side effects including nausea, vomiting, diarrhea, headache, rhinitis, myalgia, pharyngitis, abdominal pain, dyspepsia, and eye disorders. Chronic exposure to RPZ has also been associated with significant biochemical and hematological alterations, as well as various toxicological effects such as hypergastrinemia, hyperplasia, atrophy of gastric glands, gastric anti-secretory effect, and hypochlorhydria. The laboratory analysis showed that RPZ-Na concentration-dependently inhibited root length of A. cepa and A. sativum, as well as shoot and root lengths of C. arietinum. Conclusions: This study highlights the toxicological impacts of RPZ and its formulations on human and animals. Results suggest that RPZ-Na has a concentration-dependent toxic effect on A. cepa, A. sativum, and C. arietinum. Therefore, it is important to take adequate precautions during its long-term use.